Gueto Jornalístico - Sousa, Karina Custódio (Universidade Federal do Tocantins, 2022)
The objective of this work was to create a product published on the Instagram Social Network about public policies for the LGBTIA+ population in the city of Palmas, Tocantins, called Gueto Jornalístico. In order to investigate the existence of public policies for this population in the city, as well as expose the violence suffered by LGBTIA+ people and the social actors involved in public policies for LGBTIA+ people. To achieve the established objectives, bibliographical and documental research, semi-open interviews and market research were carried out in order to verify the interest in the product. The final product had 83 publications on Instagram, 65 of them on Storys, 11 on Feed, 4 IGTV, and one Live and one Reels. Throughout the work it was possible to identify the difficulties of conducting a journalistic investigation at a distance, but also to realize the potential of producing journalism on Instagram, the features offered allowed to build innovative proposals for journalistic content.